Deliverable 3.1 Assessment of EU-level deliberative and participatory practices through an intersectional lens - Huttunen, Janette; Korventausta, Miikka; Leino, Mikko; Setälä, Maija (My University, 2026)
This study develops an intersectional evaluation framework for analysing EU-level deliberative and participatory practices (DPPs) for youth engagement and applies it to 20 DPPs at the EU level. The framework is influenced by the 'Literature Review and Knowledge Integration Report' (D2.1) published as a part of SINCRONY Work Package 2 and includes four key dimensions: external inclusion, internal inclusion, intersectional purpose, and output. By using this framework as an intersectional lens, the study introduces a new approach to examining how inclusion and intersectionality measures are implemented within existing EU-level practices for political engagement. The findings indicate that the foremost way intersectionality and inclusion are promoted in EU-level DPPs is by offering support for participation. This finding suggests that the evaluated DPPs strive to empower the young participants as democratic citizens and enhance their civic skills and capabilities. The least common approaches to promoting inclusion and intersectionality were found in the intersectional purpose dimension and inclusion in recruitment. The intersectional purpose dimension entails measures such as "reclaiming the power" by the practice being youth-led or youth-initiated, and seeking institutional changes in public, political institutions, schools, or other organisations. These measures were often absent in the evaluated practices. While the results should not be considered a definitive assessment of each analysed case, the study identifies best practices that could guide the development of new DPP designs. It also provides valuable insights on aspects of inclusion and intersectionality that are generally less acknowledged, suggesting areas where future efforts could be focused to enhance inclusivity and impact.